Analysis of the Influence of Leadership and Work Motivation on Employee Productivity at PT. X - Yusuf Yusuf; Aries Widya Gunawan (Economics And Business Management Journal ( EBMJ ), 2025)
This study aims to analyze the effect of leadership and work motivation on employee productivity at PT. X. The research method used is quantitative with a verificative approach, employing multiple linear regression analysis. The sample consists of 54 employees selected using random sampling. The results show that leadership does not have a significant effect on employee productivity (p > 0.05), while work motivation has a positive but marginal effect (p < 0.1). Simultaneously, leadership and work motivation do not significantly affect employee productivity (p > 0.05). The coefficient of determination (R²) value of 0.083 indicates that only 8.3% of the variation in employee productivity can be explained by these two variables. This study suggests that PT. X should improve leadership quality and focus on enhancing work motivation to increase employee productivity.